Efficacy of Melatonin in Animal Models of Subarachnoid Hemorrhage: A Systematic Review and Stratified Meta-Analysis - Hu, Xiangyu; Zhu, Yuwei; Zhou, Fangfang; Peng, Cuiying; Hu, Zhiping; Chen, Chunli (Frontiers in Neurology, 2021)
Background and Purpose: Subarachnoid hemorrhage (SAH) is a severe disease characterized by sudden headache, loss of consciousness, or focal neurological deficits. Melatonin has been reported as a potential neuroprotective agent of SAH. It provides protective effects through the anti-inflammatory effects or the autophagy pathway. Our systematic review aims to evaluate the efficacy of melatonin administration on experimental SAH animals and offer support for the future clinical trial design of the melatonin treatment following SAH. Methods: The following online databases were searched for experimentally controlled studies of the effect of melatonin on SAH models: PubMed, Web of Knowledge, Embase, and China National Knowledge Infrastructure (all until March 2021). The melatonin effect on the brain water content (BWC) and neurological score (NS) were compared between the treatment and control groups using the standardized mean difference (SMD). Results: Our literature identified 160 possible articles, and most of them were excluded due to duplication (n = 69) and failure to meet the inclusion criteria (n = 56). After screening the remaining 35 articles in detail, we excluded half of them because of no relevant outcome measures (n = 16), no relevant interventions (n = 3), review articles (n = 1), duplicated publications (n = 1), and studies on humans or cells (n = 2). Finally, this systematic review contained 12 studies between 2008 and 2018. All studies were written in English except for one study in Chinese, and all of them showed the effect of melatonin on BWC and NS in SAH models. Conclusion: Our research shows that melatonin can significantly improve the behavior and pathological results of SAH animal models. However, due to the small number of studies included in this meta-analysis, the experimental design and experimental method limitations should be considered when interpreting the results. Significant clinical and animal studies are still required to evaluate whether melatonin can be used in the adjuvant treatment of clinical SAH patients.